Using institutional logics as cultural resources: a micro-perspective on organizational hybridity - Cortes Ferreira, Leticia (2017)
How is organizational hybridity constructed at the micro-level? This overarching question is the starting point of this doctoral research. Studies to date suggested institutional entrepreneurs can combine institutional logics to create hybrid organizations. However, simply designing an organization as a hybrid does not a hybrid organization make. Instead, unsettle times within organizations may well provide an opportunity for organizational members, other than founders and entrepreneurs, to deploy available institutional logics as cultural resources. As a consequence, hybridity is constructed as an ongoing process. Yet, little is known about the logics available to organizational members in such settings, how these logics are deployed or with what outcomes to the organization. In this thesis, I adopt a social constructionist perspective to examine the active role played by organizational members at the micro-level, in constructing organizations as hybrids. Such an approach adds to studies challenging assumptions, within the extant literature, that hybridity is imposed upon organizations, potentially negative and requiring responses or management. In order to do so, I explore a recently established Community Interest Company (CIC) to shed light on how organizational members deploy available logics in relation to organizational form and identity. Overall, my empirical research leads me to: first, refine the idea of institutional logics as cultural resources within organizations; and second, show how organizational members affect organizational hybridity by deploying logics and interacting with other organizational members, leading to different outcomes. In doing so, this research answers calls to analyse the role of the micro-level in hybrid organizational research. Furthermore, it addresses gaps in the institutional logics literature related to how, and to what end, logics are used as cultural resources in organizations, and with what organizational outcomes. On a practical note, this research can potentially support members of hybrid organizations to incorporate and balance multiple institutional and organizational aspects, achieving the positive potential of hybridity.